Perkecambahan dan pertumbuhan benih tomat (Solanum lycopersicum) akibat perlakuan berbagai dosis NaOCl dan metode pengeringan - Denanda Purba; Endang Dwi Purbajanti; Karno Karno (Journal of Agro Complex, 2018)
The purpose of the research was to study the concentration of NaOCl and drying method during the extraction process for germination and growth of tomato seedlings. This study used Completely Randomized Design with two factors with three replicates. The first factor was soaking the seeds with NaOCl concentrations: NaOCl 0% (control), NaOCl 6%, NaOCl 9% and NaOCl 13%. The second factor was the drying methods: without drying (control), natural drying and drying using oven. The parameters observed were germination, seed growth rate, maximum growth potential, leaf size, leaf area, plant height, plant growth rate and relative plant growth rate. The data were analyzed using variance analysis and continued by Duncan Multiple Range Test (DMRT) of 5%. The result of variance analysis showed that immersion treatment using NaOCl and drying method had not given interaction during seed germination and seedling growth. Soaking with 9% NaOCl showed the best result of germination process and seedling growth whereas the best drying method was naturally because it did not cause impermeability of seeds. Keyword : Tomato, seed, drying, NaOCl, seed viability